The Mexican Pension Annuity Market - Impavido, Gregorio (The World Bank, 2007)
This paper analyzes the performance and development of the Mexican pension annuity market established as a consequence of the 1997 pension reform. The Mexican experience displays interesting characteristics providing lessons for other countries that still need to design the decumulation phase of their newly established second pillars. At the same, time it raises some technical and policy concerns that need addressing as they could hamper, in the future, the healthy development of the market. The paper concludes that: 1) general life insurance companies may better hedge longevity risk than specialized annuity companies; 2) competition should be based on prices rather than additional products; 3) better disclosure of options under the 1973 and 1997 social security laws should be given to disability and life annuitants; and 4) various measures should be taken to improve asset liability management including allowing companies to trade over the counter derivatives and substituting over time the regulatory asset liability management framework with an economic asset liability management framework